Indigenous Land-Based Approaches to Well-Being: The Niska (Goose) Harvesting Program in Subarctic Ontario, Canada - Fatima Ahmed; Eric N. Liberda; Andrew Solomon; Roger Davey; Bernard Sutherland; Leonard J. S. Tsuji (International Journal of Environmental Research and Public Health, 2023)
Historically, goose harvesting provided a source of culturally significant, safe, and nutritious food for the Omushkego Cree of subarctic Ontario, Canada. Disruptions stemming from colonization and climate change have led to a decrease in harvesting, resulting in higher rates of food insecurity. The aim of the Niska program was to reconnect Elders and youth to revitalize goose harvesting activities and associated Indigenous knowledge within the community. The program and evaluation were built using a two-eyed seeing (Etuaptmumk) and community-based participatory research approach. Salivary cortisol, a biomedical measure of stress, was collected before (n = 13) and after (n = 13) participation in the spring harvest. Likewise, cortisol samples were collected before (n = 12) and after (n = 12) the summer harvest. Photovoice and semi-directed interviews were employed after the spring (n = 13) and summer (n = 12) harvests to identify key elements of well-being from an Indigenous perspective. The changes observed in cortisol levels for the spring (p = 0.782) and summer (p = 0.395) harvests were not statistically significant. However, there was a noteworthy increase in the subjective well-being observed through the qualitative measures (semi-directed interviews and photovoice), highlighting the importance of using multiple perspectives when assessing well-being, especially in Indigenous peoples. Future programs should incorporate multiple perspectives when addressing complex environmental and health issues, such as food security and environmental conservation, especially in Indigenous homelands worldwide.